Advance of Glossina morsitans submorsitans and G. pallidipes along the Ghibe-river system in southwest Ethiopia - Leak, S.G.A.; Mulatu, W. (Elsevier, 1993)
Tsetse fly populations have been monitored since January 1986 in two areas of the Ghibe valley in southwest Ethiopia, in order to assess trypanosomiasis risk to cattle. The two study areas are Abelti/Ghibe and Gullele/Tolley. Two species of tsetse fly were detected in the valley from 1986 to 1992; these were Glossina pallidipes and G. fuscipes. Both species appeared to be largely restricted to thicket vegetation along the gallery forest of the Ghibe river. In 1989, G. M. submorsitans was detected for the first time in the western, upstream study site-Gullele/Tolley. This species was not detected in the downstream, eastern area of Abelti/Ghibe until 1992. Since 1986, G. pallidipes has been found to be the most important vector of pathogenic trypanosomes to cattle in the Ghibe valley. However, G.M. submorsitans could be come more significant than G. pallidipes in the epidemiology of bovine trypanosomiasis in the area as it is a highly vector of trypanosomes and many potentially occupy a wider area of the savanna woodland in the valley than G. pallidipes.